Synthetic skull bone defects for automatic patient-specific craniofacial implant design - Jianning Li; Christina Gsaxner; Antonio Pepe; Ana Morais; Victor Alves; Gord von Campe; Jürgen Wallner; Jan Egger (Scientific Data, 2021)
Measurement(s) Image Acquisition Matrix Size • Image Slice Thickness • craniofacial region Technology Type(s) imaging technique • computed tomography Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13265225